Government Policy on Accessibility of Persons with Disabilities in Finding Jobs in Pematangsiantar City - Alyunzira Wardani; Zulkifli Zulkifli; Indra Fauzan (Budapest International Research and Critics University, 2021)
This study aims to determine the Government Policy on Accessibility of Persons with Disabilities in Finding Jobs in Pematangsiantar City. this research uses a qualitative approach. The result of this study shows Government policies related to the accessibility of persons with disabilities in obtaining employment in Pematangsiantar City are not yet fully available. This can be seen from the unavailability of programs for handling persons with disabilities from the P3A Social Service in the form of social assistance, skills training, and social advocacy for the fulfillment of the rights of persons with disabilities. Programs from the Manpower Office are not yet available, namely the lack of advocacy carried out by the Manpower Office regarding the marketing of workers with disabilities, the availability of job vacancies information, the provision of job fairs, and training programs for disabilities that are still planned but have not been realized. The program from the Regional Personnel Agency (BKD) has not met the 2% quota for employing persons with disabilities.